2019
DOI: 10.3390/s19245522
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Condition-Independent 3D Joint Angle Estimation Using Inertial Sensors and Kinematic Constraints

Abstract: In biomechanics, joint angle estimation using wearable inertial measurement units (IMUs) has been getting great popularity. However, magnetic disturbance issue is considered problematic as the disturbance can seriously degrade the accuracy of the estimated joint angles. This study proposes a magnetic condition-independent three-dimensional (3D) joint angle estimation method based on IMU signals. The proposed method is implemented in a sequential direction cosine matrix-based orientation Kalman filter (KF), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…It should be noted that the slow spine movements in this study will rely more on the stabilisation of the accelerometers, whereas the high pace but less broad movements of walking and running rely more on the quick response of the gyroscopes. A recent study by Lee & Jeon (2019) obtained very promising results by excluding the magnetometer data and applying kinematic constraints, reaching a RMSE of 1.58 . These results are not fully comparable with the present study, as the Kalman filter used in the presented was not customisable and raw data were inaccessible to the authors.…”
Section: Discussionmentioning
confidence: 98%
“…It should be noted that the slow spine movements in this study will rely more on the stabilisation of the accelerometers, whereas the high pace but less broad movements of walking and running rely more on the quick response of the gyroscopes. A recent study by Lee & Jeon (2019) obtained very promising results by excluding the magnetometer data and applying kinematic constraints, reaching a RMSE of 1.58 . These results are not fully comparable with the present study, as the Kalman filter used in the presented was not customisable and raw data were inaccessible to the authors.…”
Section: Discussionmentioning
confidence: 98%
“…It should be noted that the slow spine movements in this study will rely more on the stabilization of the accelerometers, whereas the high pace but less broad movements of walking and running rely more on the quick response of the gyroscopes. A recent study by Lee & Jeon (2019) obtained very promising results by excluding the magnetometer data and applying kinematic constraints, reaching a RMSE of 1.58°. These results are not fully comparable with the present study, as the Kalman filter used in the presented was not customisable and raw data were inaccessible to the authors.…”
Section: Discussionmentioning
confidence: 98%
“…The human body has constrained degree of freedom and temporal coherence and smoothness is an important feature of human motion. Many existing kinematic or inverse kinematic based i-Mocap frameworks, therefore uses predefined constraints to reduce measurement errors or drifts [2][3][4][5][6]. In past research [7][8][9], a small set of inertial sensors is shown to estimate 3D pose to a reasonable accuracy.…”
Section: Introductionmentioning
confidence: 99%